2011
DOI: 10.1523/jneurosci.6165-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Visual Pathways MediateDrosophilaLarval Light Avoidance and Circadian Clock Entrainment

Abstract: Visual organs perceive environmental stimuli required for rapid initiation of behaviors and can also entrain the circadian clock. The larval eye of Drosophila is capable of both functions. Each eye contains only 12 photoreceptors (PRs), which can be subdivided into two subtypes. Four PRs express blue-sensitive rhodopsin5 (rh5) and eight express green-sensitive rhodopsin6 (rh6). We found that either PR-subtype is sufficient to entrain the molecular clock by light, while only the Rh5-PR subtype is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
121
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 43 publications
10
121
0
Order By: Relevance
“…6C and Movie S6). We hypothesize that the opaque cephalopharyngeal skeleton restricts the accessibility of incident light onto the BO, effectively forming a pigment cup eye (17,24), as has been proposed in Calliphora larvae (25). When an animal is crawling with a 180°heading or a 0°heading relative to the incidence of light, it experiences a relative minimum or maximum of apparent luminosity, respectively (Fig.…”
Section: Significancementioning
confidence: 82%
See 4 more Smart Citations
“…6C and Movie S6). We hypothesize that the opaque cephalopharyngeal skeleton restricts the accessibility of incident light onto the BO, effectively forming a pigment cup eye (17,24), as has been proposed in Calliphora larvae (25). When an animal is crawling with a 180°heading or a 0°heading relative to the incidence of light, it experiences a relative minimum or maximum of apparent luminosity, respectively (Fig.…”
Section: Significancementioning
confidence: 82%
“…The BO is comprised of 12 PRs; eight express Rh6, and four express Rh5. We and others have found that the Rh6 cells are dispensable for phototaxis (17). All PRs extend their axons to the larval optic neuropil (LON).…”
Section: Significancementioning
confidence: 92%
See 3 more Smart Citations